PENGEMBANGAN EKONOMI BERBASIS SYARIAH DI ERA DIGITAL: ANTARA PELUANG, TANTANGAN, DAN KENDALA - Afwadzi, Benny; Djalaluddin, Ahmad (Journal of Sharia Economics, 2024)
A Sharia-based economy faces problems that take work. Not only is there minimal public knowledge, which has resulted in the assumption of equality between Sharia economics and conventional economics but there has also been a decline in Sharia economics in Indonesia. Not to mention the era of digitalization, which has completely changed Sharia economic practices; based on this, this article examines the development of Sharia-based economy in the digital era. The study is limited to aspects of opportunities, challenges, and obstacles. This article aims to understand the context of Sharia economics and how development must be implemented. Using a qualitative approach with library research method, the authors find that Sharia economics is an economy based on Islam. It must adopt digitalization today. Regarding several Sharia economic opportunities in the digital era, namely the Indonesian community as the largest Muslim community and product promotion in digitalization, the challenges are human resources and cyber security. At the same time, the obstacles are minimal public awareness and technological limitations. These opportunities, challenges, and obstacles have implications for the development of the Sharia economy, which must rely on digital aspects with all their shortcomings.